Association of KISS1 Gene SNPs (rs12998) With Endocrine Parameters in Iraqi women Polycystic Ovary Syndrome (Journal of Pharmaceutical Negative Results, 2022)
background: (PCOS) is among the most common types of gynecological hormonal abnormalities and metabolic problems that have an impact females throughout adolescence, with a prevalence of 6-10%.Hyperandrogenism, unreliable menstrual periods, and polycystic ovaries are the hallmarks of PCOS. The (HPG) axis is controlled by kisspeptins, peptides made by the KISS1 gene.Objectives: This investigation's objective about used to be to analyze the affiliation of kiss1 Gene SNPs (rs 12998 ) with Endocrine Parameters in PCOS .Methodology: A case -control find out about enrolled one hundred sixty members of which eighty female have PCOS and eighty symbolize the manage crew who had-been interestingly healthful. Patients with PCOS had been chosen patients from our health center and the teaching hospital's gynecology and obstetrics department in Tikrit. Assessment of serum ( kisspeptin, estradiol ,LH, FSH and testosterone) used to be performed the use of ELISA approach and the maker company's provided methodology was followed to extract genomic DNA from whole blood. KISS1 Gene SNPs rs12998 T>C gene polymorphisms was once detected by using (T-ARMS-PCR) method.Results: Findings indicate, the frequency of the kiss1 gene rs12998 CT and TT genotypes in PCOS-affected women increased 1.63-fold and 8.88-fold in comparison to the group of healthy women which have odds ratio (OR); 1.63 and 8.88, 95% [CI], 0.667-3.988 and 2.014-39.222; p-value 0.28 & 0.01**), respectively. The levels of Kisspeptin, LH, and testosterone also differ.Conclusions: Our find out about suggests a greater awareness of Kisspeptin serum levels were observed in PCOS as in contrast with healthy as well, the frequency of homozygous allele (CC) used to be greater in patient 15 than in controls 3 whilst the frequency of heterozygous allele (CT) have been now not drastically distinct in PCOS fifty six much less than the controls sixty one The allelic frequency of SNP rs12998 C/T used to be detected extra regularly with significant affiliation in female with PCOS than in